Salivary pathogen and serum antibody to assess the progression of chronic periodontitis: a 24‐mo prospective multicenter cohort study. (20th January 2016) - Morozumi, T.; Nakagawa, T.; Nomura, Y.; Sugaya, T.; Kawanami, M.; Suzuki, F.; Takahashi, K.; Abe, Y.; Sato, S.; Makino‐Oi, A.; Saito, A.; Takano, S.; et al.
Abstract : Background and Objective: A diagnosis of periodontitis progression is presently limited to clinical parameters such as attachment loss and radiographic imaging. The aim of this multicenter study was to monitor disease progression in patients with chronic periodontitis during a 24‐mo follow‐up program and to evaluate the amount of bacteria in saliva and corresponding IgG titers in serum for determining the diagnostic usefulness of each in indicating disease progression and stability. Material and Methods: A total of 163 patients with chronic periodontitis who received trimonthly follow‐up care were observed for 24 mo. The clinical parameters and salivary content of Porphyromonas gingivalis, Prevotella intermedia and Aggregatibacter actinomycetemcomitans were assessed using the modified Invader PLUS assay, and the corresponding serum IgG titers were measured using ELISA. The changes through 24 mo were analyzed using cut‐off values calculated for each factor. One‐way ANOVA or Fisher's exact test was used to perform between‐group comparison for the data collected. Diagnostic values were calculated using Fisher's exact test. Results: Of the 124 individuals who completed the 24‐mo monitoring phase, 62 exhibited periodontitis progression, whereas 62 demonstrated stable disease. Seven patients withdrew because of acute periodontal abscess. The ratio of P. gingivalis to total bacteria and the combination of P. gingivalis counts and IgG titers against P. gingivalis were significantly related to the progression of periodontitis. The combination of P. gingivalis ratio and P. gingivalis IgG titers was significantly associated with the progression of periodontitis ( p = 0.001, sensitivity = 0.339, specificity = 0.790). Conclusions: It is suggested that the combination of P. gingivalis ratio in saliva and serum IgG titers against P. gingivalis may be associated with the progression of periodontitis.